(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Man has entered in the new millennium with great hope andcelebrations. But he finds himself under severe strain and feels compelled tosit up and reassess his environment, nature. culture and future. Humanity istruly at the crossroads. Even the most powerful nations on the earth are livingunder constant shadow of terrorism. Both capitalism and socialism miserablyfailed in solving the problems of’ the masses. down-troden and deprived sectionof the society. The whole world is in search of an alternative. Gandhismprovides an answer. Gandhism is new hope, new force and above all a newchallenge in the modern world. Infact, Gandhism becomes global necessity forpeace. prosperity, freedom, harmony and survival of the hole human race.